Mortalidade infantil em município do interior do Estado de Sâo Paulo. - Poles, Kátia; Parada, Cristina Maria Garcia de Lima (My University, 2002)
Considering that infant mortality indicates the levels of health in the population, we have accomplished the foolwing work, which goals were to identify the causes of infancy mortality during the year of 1998 in Botucatu. The rate of infanty mortality obtained was as much as 12/1000 born alive with greater participation of the neonatal deaths-8,3/1000 born alive. Though most of deaths can be classified as reducible or partially reducible, but the necessary attention to make such reduction possible has varied. All the deaths that have occurred, 21.7% were classified as unavoidable, emphasizing that to reduce the rates of infant mortality, we must continue investing on the quality of health assistance as well as on the improvement of life conditions of the population.
Infant mortality in a municipality of the interior of the State of Sao Paulo